Effects of Project-Based Instructional Strategies on Colleges of Education Students’ Achievement, and Retention in Electronics Technology in North-East Nigeria - Zechariah, Ishaku; Tumba, Ishaya (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
This study examined the Effects of Project-Based and Blended Instructional Strategies on Colleges of Education Students’ Achievement, Skills Acquisition and Retention in Electronics Technology in North-East Nigeria. College of Education is one of the tertiary institutions in Nigerian alongside other institutions like polytechnics, monotechnics etc. However, Colleges of Education are the institutions that are exclusively saddled with the responsibility of training teachers who will in turn teach at the Junior Secondary School level of education in Nigeria. They are expected to realise the objectives of NCE (T.) This implies that the graduates should invariably be technologist as well as agents of technological advancement both in the classroom and in the society. In the classroom, the NCE (T) teachers should keep in step with Educational Technology materials and strategies that are applicable to their discipline and level of training. Three research questions and three hypotheses were formulated to guide the study. The study adopted Quasi -experimental design involving pre-test post-test control group. The population of the study was 73 Electronics Technology students in six Colleges of Education North-East Nigeria. The sample was 36 Electronics Technology students in three Colleges of Education. Digital Electronics Achievement Test (DEAT), Digital Electronics Retention Test (DERT) and Digital Electronics and DERT were tested for internal consistency using Pearson Product Moment Correlation. The reliability coefficients of the instruments were found to be 0.915 and 0.895 respectively Data were collected and analysed using SPSS the research questions were answered using mean, standard deviation while t-test, ANCOVA and ANOVA statistical tools were used to test the null hypotheses at 0.05 level of significance. The results showed that there was significant difference in achievement test scores between ProBaIS and TIS strategy in favour of ProBaIS. More so, the results show significant differences in students’ achievement retention in favour of ProBaIS. Study also revealed that there was no significant difference in achievement test scores of male and female students when taught Digital Electronics Using ProBaIS. It was Recommended that ProBaIS should be encourage in Colleges of Education Electronics Lesson Delivery.